Bustos virus, a new member of the negevirus group isolated from a Mansonia mosquito in the Philippines - Fujita, Ryosuke; Kuwata, Ryusei; Kobayashi, Daisuke; Bertuso, Arlene Garcia; Isawa, Haruhiko; Sawabe, Kyoko (Archives of virology, 2017)
We isolated two distinct viruses from mosquitoes collected in Bustos, Bulacan province, Philippines, in 2009. These viruses show rapid replication and strong cytopathic effects in mosquito C6/36 cells. Whole-genome analysis of these viruses demonstrated that both viruses belong to the negevirus group. One of the viruses, from Culex vishunui mosquitoes, is a new strain of Negev virus. The other virus, from a Mansonia sp. mosquito, is a new negevirus designated Bustos virus. Gene expression analysis of the Bustos virus revealed that infected cells contain viral subgenomic RNAs that probably include open reading frame (ORF) 2 or ORF3. Purified Bustos virus particles contained at least three proteins, and the major component (a probable major capsid protein) is encoded by ORF3. Bustos virus did not show infectivity in mammalian BHK-21 cells, suggesting that it is an insect-specific virus, like other known negeviruses.